Czy nauczanie zdalne jest panaceum na obecne wyzwania w nauczaniu etyki biznesu? - Horodecka, Anna (Annales. Etyka w Życiu Gospodarczym, 2020)
The scope of the paper is to investigate whether e-learning is a good alternative to achieve business ethics teaching goals in the challenging context of disembedded economies. To achieve this goal, I used various interdisciplinary methods and approaches, content analysis of the relevant literature, and a case study. Firstly, I focus on the current challenges of business ethics teaching. Then, based on my experience of teaching business ethics in various forms, I distinguish the methods applied within them and evaluate them, taking as criteria the cognitive, applicative, and reflective goals of teaching business ethics. Models and theories of educational psychology provide a framework to distinguish some elements that are responsible for the learning success of the student in terms of the defined teaching goal. Empirical results show that although e-learning scored best when it comes to achieving three differentiated goals of business ethics teaching, it is followed closely by seminars. This leads to the conclusion that perhaps a hybrid form, containing e-learning and seminars, would be the optimal way to achieve the goals.